The pedagogical strength of a Christian methodology in philosophical historiography - Seerveld, C. G. (Koers, 1975)
The kinds of problem s intrinsic to historiography and to philosophical historiography in particular are compounded when the question must be settled on how to teach the history of philosophy. For then, if one’s methodology for philosophical historiography is defective, simplistic or indecisive on the crucial matters, its exercise in the classroom will botch the philosophical development of a whole new generation.